Preparation and characterization of liprotides prepared from protein extracts of mung beans (Vigna radiata (L.)) - David, Ericsson A (Animo Repository, 2023)
In recent years, liprotides, which are protein-fatty acid complexes with core-shell structures, have proven to be promising drug carriers for cancer treatment. Due to their novel nature, there are limited studies surrounding liprotides, especially one synthesized from plant-based proteins. Thus to explore new possibilities for liprotide synthesis, mung bean albumins and globulins were each extracted and combined with oleic acid (OA) at different temperatures (40 °C and 80 °C) to synthesize four variations of plant-based liprotides (Alp40, Alp80, Glp40, and Glp80). These, along with OA and protein controls, were characterized through ATR-FTIR spectroscopy, visual stability testing, particle size analysis, and zeta potential analysis. Firstly, the IR spectra of the liprotides compared to the controls suggested that the OA molecule was encapsulated within the protein shell as intended. Peak shifts in characteristic absorption bands were also observed, indicating possible structural changes that may or may not be correlated to liprotide formation. Secondly, visual stability testing revealed that after approximately one week of being dispersed in PBS, the formation of aggregates was observed, which may indicate protein degradation due to thermodynamic alterations within their native structure. Thirdly, particle size analysis showed that the synthesized liprotides had significantly larger diameters than those indicated in published data and were highly polydispersed (PdI > 0.4). Lastly, zeta-potential analysis of the samples revealed that the oleic acid controls garnered a negative zeta-potential greater than -70 mV. This contrasts the zeta-potential values of both protein controls and liprotides which ranged between -23 mV and -33 mV. Albeit having lower values, they are still considered to be generally stable systems that are deemed appropriate for biological drug carriers. Specialized analyses to account for better protein isolation, liprotide synthesis, and overall characterization were recommended.